The art of flight - Watkinson, John, 1950- (Library of flight., 2016)
In this book, Author chronicles the disciplines and major technologies that allow heavier-than-air machines to take flight. He explains how airplanes actually fly via a qualitative understanding of the underlying process, rather than a heavy reliance on mathematics. After providing historical and technical background the author in turn examines aerodynamics, the power plant, flight information, control, performance, surface effect, and more. Readers are guided on a fascinating journey through the concepts and systems that make flight possible. This book will appeal to the technically-minded reader who seeks a reflective, thoughtful introduction to the concepts that allow flight. --